Isolation of a novel compound (MIMO2) from the methanolic extract of Moringa oleifera leaves: protective effects against vanadium-induced cytotoxity. (3rd July 2018) - Igado, Olumayowa O.; Glaser, Jan; Ramos-Tirado, Mario; Bankoğlu, Ezgi Eylül; Atiba, Foluso A.; Holzgrabe, Ulrike; Stopper, Helga; Olopade, James O.
Abstract: Moringa oleifera is reported to be a miracle plant, with positive effects on practically every system in the animal body. The methanolic extract of Moringa oleifera leaves was fractionated using liquid–liquid fractionation, column chromatography and preparative high-performance liquid chromatography (HPLC). Bioassay guided fractionation using Ferric Reducing Antioxidant Power (FRAP) was used to determine the fraction with the highest antioxidative power. Chemical structure was elucidated with nuclear magnetic resonance (NMR) spectroscopy. FRAP showed that the pure compound, butyl p-hydroxyphenyl-acetate (MIMO2) exhibited an antioxidant activity higher than TEMPOL (positive control). Vanadium is a metal, which as a salt has been shown to be a neurotoxicant; and was therefore used to assess the efficacy of MIMO2 in this experiment. HT22 (immortalized mouse hippocampal) cells were used for cell culture. The Comet assay showed a statistically significant reduction ( p  < .05) in DNA damage when 0.25 and 0.5 μM MIMO2 as well as 0.1 and 0.2 mg of the methanolic extract of Moringa oleifera leaves (MO) were used in combination with 200 μM vanadium (sodium metavanadate). Analogously, a reduced formation of superoxide was observed using dihydroethidium (2, 7-Diamino-10-ethyl-9-phenyl-9, 10-dihydrophenanthridine—DHE) stain after 0.5 μM MIMO2 and 0.063 mg MO were used in combination with vanadium 100 μM. MIMO2 and MO gave a statistically significant ( p  < .05) protective effect against vanadium toxicity on neuronal cells. Further assays may need to be performed to assess the extent of protection that MIMO2 may offer, and also to better understand its mechanisms of action.